Low-heating solid-state chemical synthesis of monoclinic scheelite BiVO4 with different morphologies and their enhanced photocatalytic property under visible light. (December 2016) - Liang, Zhiting; Cao, Yali; Qin, Haiyu; Jia, Dianzeng
Graphical abstract: Highlights: The monoclinic scheelite BiVO4 was firstly synthesized by solid-state chemical reaction. The addition of weak base NaHCO3 can change the morphology of BiVO4 . BiVO4 materials can exhibit excellent photocatalytic activity under visible light. Abstract: The monoclinic scheelite BiVO4 with different morphologies were synthesized by low-heating solid-state chemical reaction method without template or organic surfactant. The addition of weak base NaHCO3 can change the morphology of BiVO4 from polyhedrons to peanut-like and rice-like shape because that the base changed the microenvironment of the reaction system, increased the nucleation rate of product and hindered the further growth of the original product particle in process of solid-state reaction. Among the as-fabricated BiVO4 samples, the rice-like sample showed the best photocatalytic activity of 98.2% degradation for methylene blue solution after irradiation of 2 h under visible light, which attributed to the efficient separation of photoexcited electrons and holes that improved the quantum efficiency during the photodegradation process. With the help of scavengers, OH and O 2− were proved to be the main reactive species for the degradation of methylene blue.